Nurses’ Knowledge, Attitude, and Practice toward Immobility Complications: A Scoping Review - Alhassoon, Amani; Alharazi , Ruba; Almutary , Hayfa (Journal of Liaquat University of Medical & Health Sciences, 2024)
Immobility complications are challenging for healthcare professionals because they negatively affect individuals’ overall health. Following recovery from a severe illness or accident, patients’ movement is often impaired, so they may be unable to perform activities of daily living, thus impacting their quality of life. Nurses play a proactive role in preventing immobility’s physical and mental impacts. However, several studies have suggested that nurses worldwide lack knowledge, attitude, and practice (KAP) toward immobility complications. Therefore, stakeholders must prioritize this problem to optimize healthcare provision. Accordingly, this study aimed to explore nurses’ KAP toward immobility complications. A scoping review of relevant articles utilized PubMed, Scopus, Cochrane, Web of Science, Embase, CINAHL Plus, and EBSCOhost databases. Hawker’s tool assessed the risk of bias among the included primary articles. The results were analyzed according to the KAP toward four main immobility complications: pressure injury, deep vein thrombosis, ventilator-associated pneumonia, and urinary tract infection. The database search generated a total of 1398 articles. Of them, only 39 articles met the inclusion criteria for the review. Most articles concluded that nurses’ KAP were below the expected level. Education and training were found to optimize nurses’ KAP. The KAP toward immobility complications was good among nurses with work experience, high academic grades, and prior training. These findings indicate that nursing staff should receive continuous education and in-service training to improve their KAP toward immobility complications.